1980
DOI: 10.1530/jrf.0.0580377
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and pituitary concentrations of LH, FSH and prolactin in aged female C57BL/6 mice

Abstract: Plasma and pituitary concentrations of LH, FSH and prolactin were determined by radioimmunoassay in 2-month-old (young) and 16-20-month-old (old) C56BL/6 mice. There were no statistical differences in hormonal levels between aged females in oestrus (those exhibiting a copulatory plug) and those in constant dioestrus. In the old females plasma levels of LH (P < 0.002) and FSH (P < 0.001) were significantly elevated, while levels of prolactin (P < 0.001) were significantly depressed when compared with those from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…These results are similar to those in the previous report of Nobunaga et al for IV CS mice [17] and also, with those previously described in other mouse strains : C 57 BL/6 [18] ; C 5 7 BL/6J [5,16]. The increased incidence of abnormal estrous cycles in aging mice may indicate changes in ovarian function, particularly in the secretion of estradiol [6,14].…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to those in the previous report of Nobunaga et al for IV CS mice [17] and also, with those previously described in other mouse strains : C 57 BL/6 [18] ; C 5 7 BL/6J [5,16]. The increased incidence of abnormal estrous cycles in aging mice may indicate changes in ovarian function, particularly in the secretion of estradiol [6,14].…”
Section: Discussionsupporting
confidence: 92%
“…HUANG et al (1978) demonstrated that none of the elderly female rats, in contrast to the young rats, showed signs of a cyclic change in LB and FSH levels. PARKENING et al (1980) showed that the pituitary and plasma levels of LB and FSH were increased in the aged female mouse. The increase in LB content in the aged female is the same as our finding in aged rats, but the FSH levels remained unchanged in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma prolactin (PRL) levels were determined by radioimmunoassay (RIA) using materials provided by Dr. Y.N. Sinha, as described previously [17][18][19]. The levels of luteinizing hormone (LH).…”
Section: Measurement Ofhco Binding and Hormonesmentioning
confidence: 99%